Infant Food Responsiveness in the Context of Temperament and Mothers' Use of Food to Soothe - Harris, Holly A.; Moore, Amy M.; Ruggiero, Cara F.; Bailey-Davis, Lisa; Savage, Jennifer S. (Frontiers in Nutrition, 2022)
Parents’ use of food to soothe an infants’ non-hunger related distress may impair an infants’ development of appetite self-regulation. Parents tend to use food to soothe if their infant has more ‘difficult’ temperamental tendencies. However, the role of infant appetite in this association is unclear. This study investigates the moderating effect of infant food responsiveness on cross-sectional and prospective associations between infant temperament and mothers’ use of food to soothe. Mothers (n=200) from low-income households reported their infants’ temperament (i.e., surgency, negative affect and regulation) and food responsiveness at age 4 months, and their use of food to soothe at age 4 and 6 months. Temperament × food responsiveness interactions on mothers’ use of food to soothe were examined using general linear models, adjusting for covariates. Cross-sectional associations showed that mothers used more food to soothe at 4 months for infants who were lower in negative affect and higher in food responsiveness (negative affect × food responsiveness interaction: p=0.03). Prospective associations showed that mothers used more food to soothe at 6 months for infants who were lower in regulation and higher in food responsiveness (infant regulation × food responsiveness interaction: p=0.009). Other interactions were not significant. Infant food responsiveness was consistently associated with mothers’ use of food to soothe, independent of some temperamental dimensions. The findings highlight the salience of infant food responsiveness, both independent of and in association with temperament, on mothers’ use of food to soothe.